1996
DOI: 10.2141/jpsa.33.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effective Use of Shochu Distillery By-product as a Source of Broiler Feed.

Abstract: Three experiments were conducted to examine the possibility of the potential use of shochu distillery by-product (SDBP) as a feedstuff of broiler chickens.In experiment 1, 12-day-old broiler chicks were given diets containing 0, 0.7, 1.4 and 2.3% SDBP (wet), respectively.In experiment 2, 6-day-old broiler chicks were given diets containing 0.7% SDBP (wet), 1.4% wet supernatant of SDBP, 0.14% dried ether extract of SDBP and 0.28% ether extract residue, and in experiment 3, 12-day-old broiler chicks were given d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 10 publications
2
12
0
1
Order By: Relevance
“…1) We have found that SDBP contains a growthpromoting factor active in broiler chickens. 2) We have also found that SDBP feeding increased muscletocopherol and glycogen contents and decreased muscle tiobarbituric acid reactive substance (TBARS), 3) indicating that broiler chicken meat quality can be improved by SDBP. This is because SDBP contains large amounts of polyphenols and vitamins C and E.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…1) We have found that SDBP contains a growthpromoting factor active in broiler chickens. 2) We have also found that SDBP feeding increased muscletocopherol and glycogen contents and decreased muscle tiobarbituric acid reactive substance (TBARS), 3) indicating that broiler chicken meat quality can be improved by SDBP. This is because SDBP contains large amounts of polyphenols and vitamins C and E.…”
mentioning
confidence: 73%
“…We have found that SDBP contains a growthpromoting factor active in broiler chickens, 2) and that it can be extracted with ether.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…SDBP contains high amount of protein, vitamins E and C in addition to growth promoters (Mahfudz et al, 1996a(Mahfudz et al, , b, 1997. It is also the merit that it is very acidic because citric acid is produced during the fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, many methods have been developed to effectively utilize SDB. For example, there have been reports on the use of SDB as dried feed or fertilizer (Shimoda et al, 1995), a growth promoter for broilers (Mahfudz et al, 1996), a seasoning (Yokoyama et al, 2001) and in anticancer food (Sasaki et al, 2005). SDB contains an abundance of cereal-and microbial-derived nutrients, and its composition varies depending on the raw material, raw material formula and distillation method.…”
Section: Introductionmentioning
confidence: 99%